Prevalence of pelvic floor disorder and associated factors among women in Arba Minch Health and Demographic Surveillance Site, Gamo Zone, Southern Ethiopia, 2021 - Kebede, Berhanu Negese; Hayelom, Desta Haftu; Birgoda, Gebremaryam Temesgen; Yimer, Awol Arega; Mesfin, Bezawit Afework; Tetema, Mesfin Difer; Alemu, Solomon Seyife; Getahun, Kassaw Beyene (Frontiers in Urology, 2023)
Background: Globally, millions of women have developed pelvic floor disorder. It imposes a considerable emotional, social, and financial burden on women's lives. Despite this, in developing countries, nearly half of the women with pelvic floor disorder did not seek any help due to feelings of isolation, depression, shame, and loss of control. Thus, the magnitude of the problem is largely unknown. The aim of this study was to assess the prevalence of pelvic floor disorder and associated factors among women at Arba Minch Health and Demographic surveillance site. Methods: A cross-sectional study with a simple random sampling technique was employed on a community basis. The data was entered into Epi data version 3.1 software and then exported to Statistical Package for Social Sciences version 25 software for data cleaning and analysis.Bivariate and multivariable analyses using binary logistic regression were carried out to identify factors associated with pelvic floor disorder. The level of significance was declared at a p-value of < 0.05.The prevalence of pelvic floor disorder was 31.4% (95% CI: 26.9, 35.8). Being grand multi para (AOR =3.919,, having a history of instrumental delivery (AOR = 3.042, 95% CI=1.483-6.241), having a history of perianal tear (AOR= 2.972, 95%CI=1.491-5.927), and having the medical disease (AOR= 2.698, 95%CI=1.526-4.770) were factors associated with pelvic floor disorder.The prevalence of pelvic floor disorder is high in the study area. Parity, instrumental delivery, perianal tear, and medical problems were factors affecting the 2 prevalence of pelvic floor disorder. There is a need for an improvement of policies and strategies focusing on prevention and treatment services to alleviate the problem.